Fisheries Management of Terubuk (Tenualosa macrura) with an Ecosystem Approach (EAFM) in the Bengkalis Strait, Bengkalis Regency, Riau Province - Adiwanarta, Rizki; Adriman, Adriman; Efizon, Deni (Jurnal Perikanan dan Kelautan, 2023)
Fish resources are one of the natural resources that must be used as much as possible for the welfare of the community, especially around Riau Province, where part of its territory is a coastal area that has a wealth of marine biological resources that have the potential to be developed at present and in the future. One type of marine biological resource that has high economic value is the most abundant fish resource. The methods used in this study are the direct observation survey method, interviews, and distributing questionnaires. The data used in this research consists of primary and secondary data. Primary data is obtained from the results of observations and measurements made in the field, including interviews with respondents, while secondary data is in the form of excerpts from previous research journals and activity report documents obtained from related institutions or agencies. grouping based on composite value, i.e., domains that qualify as "moderate," namely economics, and domains that qualify for the "good" stage, namely the institutional domain, and finally the domains that qualify for the "excellent" stage are the domain of fish resources, the domain of fishing techniques, and the social domain. Therefore, the priority for improvement as well as the spotlight are given to the economic domain. The status of the best fisheries management in Bengkalis Regency as a whole is considered to be in good criterion condition (aggregate score: 71). However, specifically based on the values between domains, three groupings based on composite values can be obtained, namely, domains that qualify as "moderate," namely the economic domain and habitat and ecosystem. Domains that qualify as "good" are institutional domains and social domains. While the domains that qualify as "very good" are the domain of fish resources and the domain of fishing techniques, Domains that qualify as "good" are institutional domains and social domains.